Corporate Strategic Planning Frameworks for Community Development - Reichardt, Markus; Moshoeshoe, Mokhethi (2014)
The paper is based on exchanges and interviews with senior officials of companies that participated in the project, community leaders selected from areas touched by the industry, community development experts in different countries, and corporate social responsibility and corporate social investment practitioners with knowledge and working experience of Southern Africa. This was supported by desktop research and the study of published and unpublished literature on community development, corporate social responsibility, corporate philanthropy, corporate community relations, cause-related marketing, corporate strategy, and other relevant literature relating to the theme of the project.